Shaking table test of a half-scale three-story non-ductile RC building subjected to near-fault ground motions: Experimental and numerical modeling. (November 2022) - Sharma, Raju; Hsiao, Fu-Pei; Liu, Kuang-Yen; Pon, Carlos Eduardo
Abstract: This paper presents the shake-table tests of a half-scale, three-story, reinforced concrete (RC) vertically irregular non-ductile structure conducted at the newly constructed NCREE Tainan laboratory. The test specimen's structural components represent the configuration of an actual 17th-story building that collapsed during the 2016 Meinong earthquake. The collapsed structure was vertically irregular and had a non-ductile design. Existing old R.C. structures are vulnerable to significant earthquake events, as the columns in those structures have insufficient reinforcement and confinement, often leading to great seismic demands. Therefore, this study aims to understand the seismic behavior of vertically irregular non-ductile R.C. structures subjected to an increasing intensity of near-fault ground motion from the 1999 Chi-Chi earthquake. The structure remained stable throughout the tests, as only the columns at the first story sustained maximum damage. Non-linear time history analyses were performed to verify existing modeling parameters, i.e., ASCE 41-17 and the TEASPA model. The results from the analysis provided valuable insight into the ability of the existing modeling parameters to capture local and global responses of vertically irregular non-ductile structures. Furthermore, it was observed from the analysis results that using the TEASPA model provided better correlations between analytical and experimental results than the ASCE 41-17 model.